Nanostrategies synergize with locoregional interventional therapies for boosting antitumor immunity - Ting Luo; Kunpeng Ma; Yi Zhang; Qingwen Xue; Jie Yu; Xing-Jie Liang; Ping Liang (Bioactive Materials, 2025)
Compared with traditional surgical resection, systemic chemotherapy, or radiotherapy, locoregional interventional therapies (LITs) possess their own advantages of minimally invasive procedure and immunomodulatory effects in cancer treatment. Local ablation and intravascular interventional therapy represent excellent LIT candidate to combine with immunotherapy. Diverse nanomaterials with excellent biocompatibility show promises in modulating antitumor immunity. In this review, we summarized several immune-LIT combinations, discussed the following immunomodulatory effects, and presented the novel nanostrategies for synergizing with the combination therapy. With continuous optimization, further promotion of clinical translation will ultimately benefit patients with personalized and tailored cancer strategy.